Signage and wayfinding design : a complete guide to creating environmental graphic design systems - Calori, Chris; Vanden-Eynden, David, 1951- (Hoboken, New Jersey : John Wiley & Sons, 2015)
"Covers development of room/space numbering systems, approaches to sign typing and numbering, and message schedule management"--
Overview of Sign Coatings and FinishesChapter Wrap-Up; Gallery; Image Credits; Bibliography; Index; EULA
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Computer graphics; Communication in architectural design; Graphic arts; ARCHITECTURE -- General; Communication in architectural design; Computer graphics; Graphic arts; Electronic books